Neuromyelitis optica: phenotypic characteristics in a Brazilian case series - Del Negro, Maria Cristina; Marinho, Patricia Beatriz Christino; Papais-Alvarenga, Regina Maria (Arquivos de Neuro-Psiquiatria, 2017)
The definition of neuromyelitis optica (NMO) is still evolving. In 2015, the International Panel for NMO Diagnosis was convened to develop revised diagnostic criteria. There have been few studies on NMO in the Brazilian population. To describe the characteristics of 34 Brazilian NMO patients. To evaluate the contribution of the 2015 criteria to the diagnosis of NMO spectrum disorders (NMOSD) in 40 patients with longitudinal extensive transverse myelitis (LEMT).This is a retrospective, descriptive and analytic study.Among NMO patients, there was a predominance of women, with onset in the fourth decade of life, and AQP4-IgG seropositivity in 73.5%. The diagnosis of NMOSD was established in 37.5% of LETM patients according to AQP4-IgG positivity and in 5% of LETM patients if the AQP4-IgG result was unknown.The characteristics of this series are similar to those of other Western populations. The AQP4-IgG testing assists in the diagnosis of NMOSD.
Keywords: neuromyelitis optica; epidemiology; cross-sectional studies; enzyme-linked immunosorbent assay